Creation of Illness Meaning: A Central Concept of Spiritual Health - Fatemeh Khorashadizadeh (Mashhad University of Medical Sciences, 2016)
Viktor Frankl, a neurologist and the founder of logo-therapy (1969) stated that "will to meaning" is the basic essence of the universe (1). Logo-therapy means therapy through meaning, which is based on the premise that man has a will-to-meaning; the meaning thus lies in suffering(2). One of the most important human functions is discovering meaning in life, which is also considered as a sign of spiritual health(3). Defining illness by the patient is one of the most primary and significant implications for the formation of spiritual health(4). This study aimed to compare the Theory of Spiritual Well-being in nursing based on studies conducted in other countries with the theory of spiritual health according to Islamic teachings. Spiritual health theory is the theory of spiritual health in nursing. The main component of this holistic theory is to find the meaning of spirituality in the experience of illness. This theory can be taken into account in the care of patients in later stages, long-term chronic illnesses, and any kind of illness or injury that would challenge the person to find the purpose of life and the meaning of illness. In this theory, the patient is a person with the ability of finding the meaning of illness, which ultimately leads to their spiritual health (5). Conceptualization of spiritual health in Iran according to Islamic teachings has shown that spiritual health is a dynamic process oriented to the Creator's proximity where the patient creates the meaning of his/her illness through wise, prudent, and sincere communication with oneself, the Creator, and others. On this continuum of excellence, different levels and qualities of romantic orientation by the Creator, religious rationality, task orientation, and hereafter prospectiveness can be observed in patients, causing psychological balance during illness and attribution of characteristics to the Creator(6). Differences between the theories mentioned above are as follows: 1. In the theory of spiritual health, the patient acquires spiritual meaning of illness, while in the conceptualization of spiritual health according to Islamic teachings, the patient creates meaning of illness. This difference is rooted in the exogenous and endogenous nature of spirituality. According to religious teachings, endogenous spiritual health focuses on the creation of meaning, while being autonomous and self-standing, background-oriented and valued, spontaneous and dynamic, progressive and constructive. However, exogenous spirituality focuses on the acquisition of meaning, mental spirituality, external and artificial products, while being dependent and attached, whim-oriented and acquired, worldly and instrumental, other-motivated and static, declining and dying (7). 2. In the conceptualization of spiritual health based on Islamic teachings, the patient thinks about himself, explores his moods and thoughts, reviews his past behavior, thinks about his values ​​and beliefs, and tries to figure out whether his past behavior, moods, and thoughts have been coordinated with his value and belief systems (6, 7). 3. In the Theory of Spiritual Well-being, social support is addressed as a contributing factor for the formation of spiritual well-being. It seems that while connection with others is considered as a two-way communication in the conceptualization of spiritual health model based on, a one-way communication link has been reported between the patient and others (6). 4. Another difference in the mentioned conceptualization models is that while spiritual health conceptual model is based on Islamic teachings, the spiritual well-being conceptual model does not take components such as hereafter prospectiveness, task orientation, and mental balance into account (6). In general, it could be concluded that since the search for meaning and spiritual health are context-driven concepts, and significant differences have been observed in their conceptualization based on various cultures, it is recommended that the healthcare system pay especial attention to this crucial issue in order to effectively perform interventions and cares to promote spiritual health of patients.